2015
DOI: 10.1073/pnas.1424667112
|View full text |Cite
|
Sign up to set email alerts
|

Environmental constraints drive the partitioning of the soundscape in fishes

Abstract: The underwater environment is more and more being depicted as particularly noisy, and the inventory of calling fishes is continuously increasing. However, it currently remains unknown how species share the soundscape and are able to communicate without misinterpreting the messages. Different mechanisms of interference avoidance have been documented in birds, mammals, and frogs, but little is known about interference avoidance in fishes. How fish thus partition the soundscape underwater remains unknown, as acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 42 publications
5
100
0
Order By: Relevance
“…Some studies have suggested that species avoid competition by partitioning acoustic space in time or frequency [9][10][11][12][13][14], while others have reported temporal synchrony and spectral overlap among species [15,16]. These studies focused on individual taxonomic groups (e.g., fish [14], birds [17], insects [18] and anurans [10,12,15], so any interactions that may have shaped the observed use of acoustic space would be restricted to within a group [16]. To our knowledge, no study has assessed patterns of frequency and time use for all species in the acoustic community (0-22 kHz), and few studies have evaluated how the use of acoustic space varies across a gradient of species richness [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that species avoid competition by partitioning acoustic space in time or frequency [9][10][11][12][13][14], while others have reported temporal synchrony and spectral overlap among species [15,16]. These studies focused on individual taxonomic groups (e.g., fish [14], birds [17], insects [18] and anurans [10,12,15], so any interactions that may have shaped the observed use of acoustic space would be restricted to within a group [16]. To our knowledge, no study has assessed patterns of frequency and time use for all species in the acoustic community (0-22 kHz), and few studies have evaluated how the use of acoustic space varies across a gradient of species richness [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is possible that broad-scale community-level summaries, such as the ones presented here, mask nuanced differences among reefs that might emerge from more fine-scale assessments that examine and quantify the sounds being produced, and not just the overall trend. Indeed, the broad trends in reef soundscapes have now been described for several reef systems; however, more granular investigations looking at the occurrence patterns of individual sound types are far rarer (but see Ruppe et al, 2015). Such studies are labor intensive when manual identification of sounds is required.…”
Section: Next Stepsmentioning
confidence: 99%
“…This includes the "space" to effectively communicate with conspecifics (3). In PNAS, Ruppé et al (4) document apparent resource partitioning in the acoustic communication behavior of a community of nocturnal marine fishes found in a cave environment on the rocky coastline of South Africa. They recorded and analyzed 2,793 instances of 17 distinctive sounds that differed in peak frequency and pulsing characteristics.…”
mentioning
confidence: 99%
“…The Ruppé et al study (4) tackles several emerging topics in the area of marine soundscape research. By illuminating differences in daytime and nighttime patterns of acoustic signaling, they are contributing to a developing body of knowledge on the impact of environmental constraints such as daily and lunar cycles on marine soundscapes (e.g., ref.…”
mentioning
confidence: 99%